The Effect of Labor, Fiscal Decentralization, And Local Income On The Human Development Index Mediated By The Economic Growth Of Urban And District Areas In East Java Province In 2017-2021 - Yusuf, Muhammad (Jurnal Ekonomi Kuantitatif Terapan; 2023: Vol. 16, No. 1, Februari 2023 (pp.1-186), 2023)
Indonesia`s intensively encouraging even better economic growth by the role of labor as one of the factors of production that will affect the high level of national income in terms of quality or quantity alone. The purpose of this study is to determine the effect of labor, fiscal decentralization, and local income on the human development index mediated by the economic growth of urban and district areas in east java province in 2017-2021. The quantitative research method was applied in this research with Explanatory Research, which employs hypothesis testing to explain the correlation among independent and dependent variables. The population in this research was the City of East Java Province in the research period during the period 2017 – 2021 . The determination of the number of samples used by researchers is by the census method. The data employed in this stud y is secondary data using panel data from 2017 – 2021. The analysis technique carried out is the Model Moderator Regression Analysis (MRA), with the help of SPSS version 26 application. This study concludes that the Labor variable has an influence on the Human Development Index, the Fiscal Decentralization variable has no effect on the Human Development Index, the Local Revenue variable has an influence on the Human Development Index, the Regional Economic Growth variable has no influence on the Human Development Index, the Labor variable has an influence on Regional Economic Growth, the variable Fiscal Decentralization has no effect on Regional Economic Growth, the Local Revenue variable has no influence on Regional Economic Growth, the Regional Economic Growth variable cannot mediate the influence of Labor on the Human Development Index, the Regional Economic Growth variable cannot mediate the effect of Fiscal Decentralization on the Human Development Index and Regional Economic Growth variables cannot mediate the effect of Local Revenue on the Human Development Index.